An Analysis of Directive Speech Act Used by The Main Character in Deadpool & Wolverine (2024) Film - Nina Maulidya Rachman; Muhammad Alim Akbar Nasir (Fakultas Ilmu Budaya Universitas Mulawarman, 2026)
This research aims to analyze the types of directive speech acts represented by the main characters in the film Deadpool & Wolverine (2024). This study applies the theory of directive speech acts proposed by Searle and Vanderveken (1985). The purpose of this research is to examine the directive speech acts used by the two main characters, Deadpool and Wolverine. This research employs a descriptive qualitative method. The research data consist of utterances taken from the characters dialogues in the film, analyzed using Illocutionary Force Indicating Devices (IFIDs). The data were collected by watching the film, reading the script, and identifying as well as categorizing the utterances. Based on the analysis, the researcher identified thirteen of directive speech acts out of twenty-four examined in the theory. These types include request, ask, urge, tell, demand, command, order, forbid, prohibit, suggest, warn, advise and beg. The results show that command is the most frequently used directive speech act, which indicates that the main characters often employ directives to assert control, express urgency, and influence actions within interactional situationsKeywords: Linguistics, Pragmatics, Speech Act, Directive Speech Act